The Influence Of Go Food Usage, Business Duration, And Education Level On The Income Of Culinary Businesses In Denpasar City - Putu Ayu Meidha Suwandewi; Made Santana Putra Adiyadnya; Komang Ayu Trisantika Dewi (Green Publisher Indonesia, 2024)
Economic growth, poverty, and unemployment are long-term issues faced by every country. How to reduce these rates is a primary concern for governments striving to achieve success in economic development. One approach to decreasing unemployment and poverty rates is by promoting home businesses, commonly known as MSMEs (Micro, Small, and Medium Enterprises). This research aims to determine the impact of Go-Food usage, the duration of the business, and the education level on the income levels of culinary businesses in Denpasar City. The rapid development of MSMEs has a positive impact on the economy. In this study, the author focuses on MSMEs in the culinary sector in Denpasar City. The culinary business is the fastest-growing sector in Denpasar compared to other sectors. This research is located in Denpasar City, focusing on culinary businesses in the area. The sample is determined using accidental sampling techniques. Data analysis is conducted using multiple linear regression, with simultaneous and partial testing. The results of data processing using SPSS show that the variables of Go-Food usage, business duration, and education level have a positive impact on the income of culinary businesses in Denpasar City.